Re-testing theories on the correlations of health status, life satisfaction and happiness - Bourne, Paul Andrew (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: Empirical evidences have shown that happiness, life satisfaction and health status are strongly correlated with each other. In Jamaica, we continue to collect data on health status to guide policies and intervention programs, but are these wise? AIMS: The current study aims to fill the gap in the literature by examining life satisfaction, health status, and happiness in order to ascertain whether they are equivalent concepts in Jamaica as well as the coverage of the estimates. MATERIALS AND METHODS: The current study used a cross-sectional survey of 2000 men 55 years and older from the parish of St. Catherine in 2007 which is it also generalizable to the island. A132-item questionnaire was used to collect the data. The instrument was sub-divided into general demographic profile of the sample; past and Current Good Health Status; health-seeking behavior; retirement status; social and functional status. Ordinal logistic regression techniques were utilized to examine determinants of happiness, life satisfaction and health status. RESULTS: Happiness was correlated with life satisfaction - Pseudo r-squared = 0.311, -2LL = 810.36, χ(2) = 161.60, P < 0.0001. Life satisfaction was determined by happiness - Pseudo r-squared = 0.321, -2LL = 1069.30, χ(2) = 178.53, P < 0.0001. H ealth status was correlated with health status age, income, education and area of residence - Pseudo r-squared = 0.313, -2LL = 810.36, χ(2) = 161.60, P < 0.0001. CONCLUSION: The current study refuted the empirical finding that self-reported happiness depends on perceived health status for older men in Jamaica.